Two-pillar monetary policy and bootstrap expectations - Heinz-Peter Spahn (Research On Money in the Economy (ROME), 2007)
The paper integrates the two-pillar Phillips curve, which explains expected inflation by the money growth trend, within a simple macro model. A Taylor-like interest rule contains also a money growth target. The model takes into account serially correlated supply and money demand shocks; the latter induce goods demand shocks, thereby establishing a feedback mechanism from money to markets which is missing in the modern New Keynesian approach. Two groups of market agents are distinguished from which one derives inflation expectations from money growth trend figures whereas the other builds rational expectations by way of learning. The inspection of output and inflation variances show that a policy of reacting to excess money growth requires precise information on shock characteristics whereas inflationgap and output-gap oriented interest policies provide more robust stabilization services.
Keywords: E4; E5; 330; Money demand shocks; Taylor rule; learning; inflation and output variability